2022
DOI: 10.1038/s41420-022-01040-2
|View full text |Cite
|
Sign up to set email alerts
|

Roles and mechanisms of the m6A reader YTHDC1 in biological processes and diseases

Abstract: N6-methyladenosine (m6A) is a key area in Epigenetics and has been increasingly focused these years. In the m6A process, readers recognize the m6A modification on mRNAs or noncoding RNAs and mediate different downstream events. Emerging studies have shown that YTHDC1, an important m6A reader, plays a key role in many biological functions and disease progression, especially cancers. Here we summarized the current mechanisms of YTHDC1 in biological functions and diseases and offered guidance for future researche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 63 publications
0
34
0
Order By: Relevance
“…Furthermore, even though YTHDC1 and DDX5 46 , 47 are both nuclear factors, we ruled out that the observed reduction of circRNAs could be related to their reduced stability by performing actinomycin D treatment in RD cells. As expected, besides the high stability of circRNAs over time (up to 12 hrs), we did not observe reduced half-life either upon YTHDC1 nor in DDX5 depletion (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, even though YTHDC1 and DDX5 46 , 47 are both nuclear factors, we ruled out that the observed reduction of circRNAs could be related to their reduced stability by performing actinomycin D treatment in RD cells. As expected, besides the high stability of circRNAs over time (up to 12 hrs), we did not observe reduced half-life either upon YTHDC1 nor in DDX5 depletion (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…YTHDC1, one of the most noted m 6 A reader, recognizes m 6 A modification on mRNAs or ncRNAs and mediates different biological processes, such as cytoplasmic export, RNA stabilization and decay [ 39 ]. Notably, YTHDC1 plays critical roles in different cancers [ 39 , 40 ], and the elevation of YTHDC1 is observed in CRC cells and tissues [ 41 ]. Recent studies have demonstrated that YTHDC1 facilitates cytoplasmic delivery of circMET in renal cell carcinoma [ 42 ], as well as the cytoplasmic translocation of circHPS5 in hepatocellular carcinoma (HCC) in an m 6 A-dependent manner [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…m 6 A modification is originally identified as a predominant modification of mRNA, and its pivotal roles in ncRNA modification have emerged recently [4,5]. YTHDC1, one of the most noted m 6 A reader, recognizes m 6 A modification on mRNAs or ncRNAs and mediates different biological processes, such as cytoplasmic export, RNA stabilization and decay [39]. Notably, YTHDC1 plays critical roles in different cancers [39,40], and the elevation of YTHDC1 is observed in CRC cells and tissues [41].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are three RBPs that have been widely studied, including YT521-B homology (YTH) domain family proteins, insulin-like growth factor 2 mRNA-binding proteins (IGF2BPs) and heterogeneous nuclear ribonucleoproteins (HNRNP) family proteins ( Liu C. et al, 2022 ). The YTH domain family proteins are important m6A methylation RBPs, which can bind to m6A and affect the outcome of m6A-methylated RNAs ( Yan et al, 2022 ). YTH proteins mainly includes YTHDFs and YTHDCs subtypes.…”
Section: Abnormal Expression Of N6-methyladenosine Modification Prote...mentioning
confidence: 99%